Toward seamless taxation through a split payment mechanism on the marketplace and Quick Response (QR) payment system - Handhung Dwi Nugroho (Directorate General of Taxes, 2023)
The rapid development in Indonesia's digital economy offers both challenges and prospects for the Directorate General of Taxes (DGT) in tax collection. Despite the intricacy of monitoring digital transactions, their electronic data can be efficiently collated. Through a desk review, the author discusses government strategies to boost tax revenue from the digital economy and suggests a split payment mechanism for marketplace transactions and Quick Response (QR) Payment Systems. This mechanism benefits both taxpayers and the DGT by simplifying tax obligations, increasing revenue, and streamlining cash flow for the latter, all at reduced supervision costs.